Comparing regional development in China and India - Yanrui Wu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Economic growth in China and India has attracted many headlines recently. As a result, the literature comparing the two Asian giants has expanded substantially. This paper adds to the literature by comparing regional growth, disparity and convergence in the two economies. This is the first of its kind. The paper presents a detailed examination of economic growth in the regions of China and India over the past twenty years. It also provides an assessment of regional disparity in the two countries and investigates whether there is any evidence of regional convergence during the period of rapid economic growth. It attempts to identify the sources of regional disparity and hence draw policy implications for economic development in the two countries in the near future.
Keywords: O57; O11; 330; regional development; China; India; disparity; convergence; Regionales Wachstum; Regionale Disparität; Entwicklungskonvergenz; China; Indien